2013
DOI: 10.1007/978-3-642-31552-7_10
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Adaptive and Intelligent Tutor by Expert Systems

Abstract: Todays, Intelligent and web-based E-learning is one of regarded topics. So researchers are trying to optimize and expand its application in the field of education. The aim of this paper is developing of E-learning software which is customizable, dynamic, intelligent and adaptive with Pedagogy view for learners in intelligent schools. This system is an integration of adaptive web-based Elearning with expert systems as well. Learning process in this system is as follows. First intelligent tutor determines learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Reference source not found.4. Reader can find more details in [2]. Believing that the experiences create learning.…”
Section: Jackson's Learning Styles Profilermentioning
confidence: 99%
See 3 more Smart Citations
“…Reference source not found.4. Reader can find more details in [2]. Believing that the experiences create learning.…”
Section: Jackson's Learning Styles Profilermentioning
confidence: 99%
“…It means that some learners need to repeat some lessons mean while some lessons must be removed for others. Later the researchers concluded that learning process must be dynamic and intelligent based on pedagogy view [2]. But developing an applicable and trustful system is so hard [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diversity of learners leads to decrease the efficiency of this style. In fact, some lessons must be repeated several times for a number of learners while the same courses may be removed for others [2].…”
Section: Introductionmentioning
confidence: 99%